Impacto do adoecimento mental sobre os afastamentos de servidores em uma Instituição Federal de Ensino Superior - Sabóia, Francimayre de Sousa (2024)
According to the WHO, in 2019, about 15% of adults of working age had a mental disorder. Mental disorders are one of the main causes of absenteeism in Brazil, and the work environment can be a source of psychosocial risk factors.The aim of this study was to understand the impact of mental and behavioral disorders (MBDs) on absenteeism among public servants in a public educational institution. To this end, this s tudy evaluated the records of absences for health treatment (or leave) due to mental and behavioral disorders at the Federal University of Ceará (UFC) from 2018 to 2023. The data was obtained from the SIASS platform (Integrated Server Health Care Subsystem). The diseases and disorders classified in the International Classification of Diseases 10 were grouped into: mental and behavioral disorders, respiratory and COVID-19 and other diseases. The data show that mental and behavioral disorders are the group of diseases that have the greatest impact on sick leave among UFC civil servants: they were the main cause of sick leave, represented the highest average number of sick days per worker, and their number is increasing. In light of these findings, we can conclude that the strategies used have not been adequate and/or sufficient and, therefore, it is proposed to implement a sustainable Quality of Life at Work Plan - from the perspective of the Psychodynamics of Work (PDT) theory - prioritizing effective changes to mitigate the phenomena that generate psychosocial risk factors that are present in the organization of the institution's work.